PEP-sNASP Peptide Alleviates LPS-Induced Acute Lung Injury Through the TLR4/TRAF6 Axis - Wu, Yu-Chih; Hsu, Sung-Po; Hu, Meng-Chun; Lan, Yu-Ting; Yeh, Edward T. H.; Yang, Feng-Ming (Frontiers in Medicine, 2022)
Acute lung injury (ALI) is a severe inflammatory lung disease associated with macrophages. Somatic nuclear autoantigenic sperm protein (sNASP) is a negative regulator of Toll-like receptor (TLR) signaling that targets tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) in macrophages, which is required to maintain homeostasis of the innate immune response. In the present study, we generated a cell permeable PEP-sNASP peptide using the sNASP protein N-terminal domain, and examined its potential therapeutic effect in a mouse model of ALI induced by the intranasal administration of lipopolysaccharide (LPS) and elucidated the underlying molecular mechanisms in RAW 264.7 cells. In vivo, PEP-sNASP peptide treatment markedly ameliorated pathological injury, reduced the wet/dry (W/D) weight ratio of the lungs and the production of proinflammatory cytokines (interleukin (IL)-1β, IL-6, and TNF-α). In vitro, we demonstrated that when the PEP-sNASP peptide was transduced into RAW 264.7 cells, it bound to TRAF6, which markedly decreased LPS-induced proinflammatory cytokines by inhibiting TRAF6 autoubiquitination, nuclear factor (NF)-κB activation, reactive oxygen species (ROS) and cellular nitric oxide (NO) levels. Furthermore, the PEP-sNASP peptide also inhibited NLR family pyrin domain containing 3 (NLRP3) inflammasome activation. Our results therefore suggest that the PEP-sNASP may provide a potential protein therapy against oxidative stress and pulmonary inflammation via selective TRAF6 signaling.